The essential gesture : writing, politics and places - Gordimer, Nadine; Clingman, Stephen (New York : Knopf, 1988)
23 essays present a portrait of South Africa from the 1950s through the 1980s.
Bibliography: p.
Booklist.
Library Journal.
Wilson's Public Library.
Adult.
Adult
Keywords: Gordimer, Nadine -- Biography; Gordimer, Nadine -- Biography; Novelists, South African -- 20th century -- Biography; Novelists, South African; South Africa -- Politics and government -- 20th century; South Africa -- Race relations; South Africa -- Politics and government; South Africa -- Race relations